X linked Charcot-Marie-Tooth disease (CMTX1): a study of 15 families with 12 highly informative polymorphisms. Issue 3 (March 1994) - Cochrane, S; Bergoffen, J; Fairweather, N D; Müller, E; Mostacciuolo, M L; Monaco, A P; Fischbeck, K H; Haites, N E
Abstract : X linked dominant Charcot-Marie-Tooth disease (CMTX1) has previously been localised to Xq13-21. Fifteen families were studied using 12 highly informative polymorphisms in the pericentric region of the X chromosome. Phase known recombinations in these families localise the X linked dominant CMT gene to the region distal to DXS106 (Xq11.2-12) and proximal to DXS559 (Xq13.1). These markers flank approximately 2 to 3 Mb of DNA to which GJB1 and CCG1 have already been mapped. A recent report of mutations in the GJB1 gene in subjects with CMTX1 makes this a strong candidate gene.